Emotional Intelligence of at Risk Students in Malaysian Secondary Schools - Elias, Habibah; Mahyuddin, Rahil; Abdullah, Maria Chong; Roslan, Samsilah; Noordin, Nooreen; Fauzee, Omar (The International Journal of Learning, 2007)
At-risk students in this study are those with low academic achievement and with behavioral problems. The study utilizes the descriptive survey method. The sample of this study comprised of 688 secondary school students who are at-risk and their average age was sixteen. Findings indicate that the mean EQ of at-risk students were rather low (mean= 57.67, SD=0.26). The mean scores for the three sub-scales of EQ among the students were 18.91 for Emotional Self-Awareness (ESA), 14.94 for Emotional Expression (EE), and 24.18 for Emotional Awareness of others (EAO). Based on the scoring grid suggested by Cooper and Sawaf (1996), both ESA and EE students were found to be vulnerable (ESA:19-23;EE:13-16), except for EAO which was found to be proficient (22-27).Research findings also indicate significant gender differences(t=4.103,p<.05) in EQ scores among at-risk students with female students obtained a higher mean compared to the males. In addition results also found positive and significant correlations between EQ and the following variables namely academic achievement (r=.195, p<.05), self-esteem (r=.361, p<.05), achievement motivation (r=.354, p<.05), Mathematics self-efficacy (r=.310,p<.05) and English self-efficacy (r=.498,p<.05). The implications of the findings are discussed in terms of educational opportunities for at-risk students.